A study of the degradation of feather and hair wastes in an eco-friendly way so as to make the waste dumping soils fertile - Ashok Patel; Shri Kohli; Prakash Kohli (African Journal of Environmental Economics and Management, 2015)
The current study was aimed at the degradation of feather and hair wastes in an eco-friendly way, which should further be helpful to make the waste dumping soils fertile. Degradation of feathers and hair was assessed by a highly potent Keratinophilic fungus namely Chrysosporium tropicum. The 60 day experiment was set up with sterile defatted feather and hair as substrates in a mineral medium along with the inoculum of the organism. The culture filtrate was analyzed every 10 days, for the release of catabolic products such as protein and keratinase, along with the concomitant increase in pH. Maximum degradation was found on the 40th day sample, where the protein released was 6.9mg/ml and the Keratinolytic activity was 8.56 KU/ml. The increase in pH (from neutral), towards alkalinity up to 40days (9.0) of incubation and decline thereafter, indicates that the release of soluble protein into the medium is maximum for 40 days. Among the two substrates used, Chrysosporium tropicum had more effect on hair than that of feather.